THE INFLUENCE OF INFLATION RATE, RETURN ON EQUITY AND DEBT TO EQUITY RATIO TOWARD STOCK PRICE OF MINING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Wiria Atmaja Kusuma; Meilani Meilani (Jurnal Penelitian Akuntansi (JPA), 2022)
Many companies in Indonesia try to grow by relying on the stocks by issuing their stocks to the public including the mining companies. In order to know which stock to buy, many investors will use the indicators. Some of the indicators that are used by the investors involve the Return on Equity (ROE) and Debt to Equity Ratio (DER). The other factor that also needs to be taken into consideration is the macroeconomic condition of a country such as Inflation Rate.               The purpose of this research is to determine the influence of Inflation Rate, Return on Equity, and Debt to Equity Ratio toward the Stock Price of mining companies listed on Indonesia Stock Exchange. The sampling method that is conducted in this research is purposive sampling method were based on this sampling method, there are 11 companies that are chosen as the samples of this research. The data analysis is this research is conducted by using multiple linear regression analysis using IBM SPSS Statistics 25.0.Based on the result of this research, it can be seen that Inflation Rate and Debt to Equity Ratio partially have insignificant influence toward Stock Price of mining companies listed in Indonesia Stock Exchange. On the other hand, Return on Equity has significant influence toward the Stock Price of mining companies listed on Indonesia Stock Exchange. It is also showed by the result of this research that Inflation Rate, Return on Equity, and Debt to Equity Ratio simultaneously have significant influence toward Stock Price of Mining Companies listed on Indonesia Stock Exchange. The percentage of contribution of Inflation Rate, Return on Equity, and Debt to Equity Ratio toward Stock Price is 52.3%. This indicate that 47.7% Stock Price is influenced by other variables. Keywords: Inflation Rate, Return on Equity, Debt to Equity Ratio, Stock Price